Penerapan Hukum Jaminan Fidusia Dalam Kontrak Pembiayaan Syariah - Muhammad Maksum (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2015)
Abstract: Application of the Contract Law of Fiduciary In Islamic Financing. Islamic finance products is almost entirely implement the guarantee. Such guarantees a careful effort as well in case when borrowers are unable to pay the debt. Customer financing at a conventional financial institution based debts so that the application of fiduciary can be applied. However, financing is not entirely based Islamic financial debts, but also based working capital and services. In the last two financing models did not reveal any debts in principle that the application of fiduciary can not fit the model of such financing. Guarantee letter (al-Rahn al-tasjili) is introduced in the form of a guarantee that Islam has similarities with fiduciary although not exactly the same. Abstrak: Penerapan Hukum Jaminan Fidusia Dalam Kontrak Pembiayaan Syariah. Produk-produk pembiayaan syariah hampir seluruhnya menerapkan jaminan. Jaminan tersebut sebagai upaya hati-hati sekaligus jaga-jaga tatkala nasabah peminjam tidak mampu membayar utang. Pembiayaan nasabah di lembaga keuangan konvensional berbasiskan utang-piutang sehingga penerapan jaminan fidusia dapat diterapkan. Akan tetapi, pembiayaan di keuangan syariah tidak seluruhnya berbasis utang-piutang, namun juga ada yang berbasis modal kerja dan jasa. Pada dua model pembiayaan terakhir tidak ditemukan adanya utang-piutang secara prinsip sehingga penerapan jaminan fidusia tidak bisa klop dengan model pembiayaan tersebut. Jaminan surat (al-rahn al-tasjili) adalahbentuk jaminan yang dikenalkan dalam Islam yang memiliki kemiripan dengan jaminan fidusia meskipun tidak sama persis. DOI: 10.15408/jch.v2i1.1837